Formação de ressonâncias Delta em estrelas de Nêutron - Fong, Chan Tat (2009)
In this work we obtained the equations of state and populations of baryons and leptons to the dense stellar matter and highly asymmetric, consisting of the octet of baryons of spin 1/2 (n, p, Λ0, Σ−, Σ0, Σ+, Ξ−, Ξ0) and barionic resonances of spin 3/2, represented by the delta resonances (∆−, ∆0, ∆+, ∆++) and Ω−, in the baryonic sector, and of the electrons (e−) and muons (µ −) in the lepton sector, using the Walecka and Zimanyi-Moszkowski models. The hadronic matter is studied using the field of Dirac, for particles of spin 1/2, and the field of Rarita-Schwinger, for particles of spin 3/2, in the context of the calculation of relativistic mean field. From the equations of state obtained for the stellar matter, we solve numerically the TOV equation (Tolman-Oppenheimer-Volkoff) to the internal structure of neutron stars by comparing their masses and radii obtained with these models. We observed that the attractive nature of the interaction of these delta resonances with other baryons present in hadronic condensed induces a gas-liquid phase transition in the condensed to typical densities inside neutron stars.